Se A=X²+1 E B=-2X²+2 , DETERMINE
A) A+B
B) A-B
Soluções para a tarefa
Respondido por
2
a)
= A + B
= x² + 1 + (- 2x² + 2)
= x² - 2x² + 1 + 2
= - x² + 3
b)
= A - B
= x² + 1 - ( - 2x² + 2)
= x² + 1 + 2x² - 2
= 3x² - 1
= A + B
= x² + 1 + (- 2x² + 2)
= x² - 2x² + 1 + 2
= - x² + 3
b)
= A - B
= x² + 1 - ( - 2x² + 2)
= x² + 1 + 2x² - 2
= 3x² - 1
Perguntas interessantes
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Geografia,
1 ano atrás
História,
1 ano atrás
Química,
1 ano atrás